Methodology for the evaluation of demand response strategies for the management of natural gas systems. (1st November 2021) - Montuori, Lina; Alcázar-Ortega, Manuel; Álvarez-Bel, Carlos
Abstract: The gradual increase in energy consumption that has been produced during the last years, together with the massive implementation of renewable generation technologies, has motivated a significant increment in the variability and unpredictability of power generation, along with the subsequent increment in the cost of grid management and higher probability of contingencies. As a result, the customers' participation in the solution of these problems by means of DR actions is more and more applied worldwide. In this framework, the existing similarities between the electricity and natural gas systems permit to expect a successful application of DR concepts for a more efficient operation of natural gas systems by using the flexibility of consumers. In order to develop DR products in the gas system, services that consumers may offer have been investigated. Therefore, the proposed methodology includes the analysis of the management actions that system operators must address in the daily management of the systems (such as balancing, pipeline congestion or reserve shortages in underground storages), the identification of DR products that have been successfully developed for power system operators or the metering and communication needs for the full exploitation of the flexibility in this sector. Graphical abstract: Image 1 Highlights: Demand Response has been commonly used in power systems, but it remains underexplored in the natural gas network. A revision of Demand Response applications in natural gas systems is presented. A methodology for the development of demand response products in the gas system is presented. The methodology considers technical, economic and environmental approaches. Operation services where demand response resources could be used in gas systems are identified.